1992
DOI: 10.1161/01.str.23.11.1566
|View full text |Cite
|
Sign up to set email alerts
|

Early time course of N-acetylaspartate, creatine and phosphocreatine, and compounds containing choline in the brain after acute stroke. A proton magnetic resonance spectroscopy study.

Abstract: Background and Purpose:The early time course after acute stroke of cerebral JV-acetylaspartate, creatine and phosphocreatine, and compounds containing choline was studied in vivo by means of localized water-suppressed proton magnetic resonance spectroscopy.Methods: Eight patients with acute stroke were studied serially in the acute phase, 1 week after, and 2-4 weeks after the onset of clinical symptoms. Ten healthy volunteers served as controls. A stimulated echo (STEAM) sequence was used for measurement of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
3
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(75 citation statements)
references
References 31 publications
2
66
3
3
Order By: Relevance
“…8 Disappearance of NAA within 24 to 48 hours after cerebral ischemia in adults has been reported. 15,16 No abnormalities were seen with diffusionweighted MRI, whereas definite changes were visible on T2-and inversion recovery-weighted images in patient E. ADC values of the globus pallidus were 1.013ϫ 10 Ϫ3 (left) and 1.057 ϫ 10 Ϫ3 mm 2 /second (right), which we consider a normal value for a term neonate. 17 In neonates with severe birth asphyxia, abnormalities can be detected by using diffusionweighted MRI during the first week after birth.…”
Section: Discussionmentioning
confidence: 75%
“…8 Disappearance of NAA within 24 to 48 hours after cerebral ischemia in adults has been reported. 15,16 No abnormalities were seen with diffusionweighted MRI, whereas definite changes were visible on T2-and inversion recovery-weighted images in patient E. ADC values of the globus pallidus were 1.013ϫ 10 Ϫ3 (left) and 1.057 ϫ 10 Ϫ3 mm 2 /second (right), which we consider a normal value for a term neonate. 17 In neonates with severe birth asphyxia, abnormalities can be detected by using diffusionweighted MRI during the first week after birth.…”
Section: Discussionmentioning
confidence: 75%
“…In fact, NAA levels are frequently found to be absent in tumors of glial origin (e.g. Sibtain et al, 2007) and to decrease in neuropathological conditions, correlating with the degree of degeneration in humans (Bruhn et al, 1989;Gideon et al, 1992Gideon et al, , 1994Horská et al, 2009;Kantarci, 2007) and rodents (e.g. Berthet et al, 2011;Lei et al, 2009;Tkáč et al, 2007).…”
Section: Neurotransmitter Metabolismmentioning
confidence: 99%
“…With further ischemia evolution, additional, more profound concentration decreases are detected, reflecting a disruption of cellular function. Thus, early changes in markers of energy metabolism, glutamate excitotoxicity, osmolarity deregulation and neuronal viability can be detected with high precision noninvasively in mice after stroke, and provide a better understanding of the sequential early changes in the brain parenchyma after ischemia ), which could be used to identify new targets for neuroprotection and defining metabolic markers of tissue viability after stroke Bruhn et al, 1989;Gideon et al, 1992Gideon et al, , 1994.…”
Section: Hypoxic and Ischemic Diseasesmentioning
confidence: 99%
“…51 MRS findings and gradual attenuation of NAA in the acute stage of ischemic stroke Typical chronological changes visible by MRS during acute ischemic stroke have been identified in several animal studies [52][53][54][55] and subsequently confirmed in human clinical studies. [56][57][58][59] Typically, chronological changes of four MRS visible metabolites can be seen following cerebral ischemia, namely rise of lactate, and attenuations of NAA, creatine and phosphocreatine (Cr), and choline compounds (Cho). Lactate appears immediately after cerebral blood flow is compromised and usually reaches a concentration plateau within 24 hours depending on several factors, such as the severity of hypoperfusion and plasma glucose concentrations.…”
Section: Concept Of Experimental Ischemic Strokementioning
confidence: 99%
“…3). 54,[56][57][58][59] After 24 hours, lactate tends to cover the entire topographical area of hypoperfusion, including the penumbra. Part of the "tissue at risk" can be identified as areas in which lactate is present but there is no attenuation of NAA (Fig.…”
Section: Concept Of Experimental Ischemic Strokementioning
confidence: 99%